2010
DOI: 10.1007/s11434-009-0722-1
|View full text |Cite
|
Sign up to set email alerts
|

Improved and excellent ethanol sensing properties of SnO2/multiwalled carbon nanotubes

Abstract: SnO 2 /multiwalled carbon nanotubes (MWNTs) have been studied as gas sensing materials. Compared with pure SnO 2 , SnO 2 /MWNTs exhibit improved ethanol sensing properties such as higher sensitivity and quicker response/recovery at 300°C. The sensitivity is 35, 65, 166 and 243 to 500, 1000, 2000 and 3000 ppm ethanol, respectively. The response time is about 1 s, and the recovery time is about 5 s. The sensing improvement is explained in terms of the appropriate basal resistance and enhanced signal transfer bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The base sensing mechanism of ZnO is similar as that of other semi-conducting metal oxides such as SnO 2 and Fe 2 O 3 , and the theoretical analyse has been clarified in many previous works [11,12]. Basically, the change in resistance of oxide gas sensors is primarily caused by the adsorption and desorption of the gas molecules on the surface of sensing films.…”
Section: Resultsmentioning
confidence: 85%
“…The base sensing mechanism of ZnO is similar as that of other semi-conducting metal oxides such as SnO 2 and Fe 2 O 3 , and the theoretical analyse has been clarified in many previous works [11,12]. Basically, the change in resistance of oxide gas sensors is primarily caused by the adsorption and desorption of the gas molecules on the surface of sensing films.…”
Section: Resultsmentioning
confidence: 85%
“…) dominate the senor response, and the resistance change of the sensors can be explained by the capture and release of electrons from the conductance band of the sensing materials [19,20]. But for low temperature sensors, their sensing mechanism is quite different.…”
Section: Resultsmentioning
confidence: 99%
“…Noteablely, recent advances demonstrated that the decoration of MWNTs with metal oxide nanoparticles or polymer was an alternative route for constructing highperformance gas sensors due to its high sensitivity, short response and recovery times and low cost. Liu et al [17] reported an ethanol gas sensor using SnO 2 /MWNTs as sensing materials at 300°C, and exhibited improved ethanol sensing properties than that of pure SnO 2 in terms of the appropriate basal resistance and enhanced signal transfer brought by MWNTs. Parmar et al [18] fabricated CuO/MWNT thin film based ethanol-sensors by dispersing CVD-prepared MWNTs in varying concentration over DC magnetron sputtered-CuO films, and the sensor exhibited enhanced sensing response at an operating temperature of 400°C compared with bare CuO sample.…”
Section: Introductionmentioning
confidence: 99%